New Locations for Discursive Agency: The Story of Anandamai Ma - Mary Ann Cain (Journal of the Assembly for Expanded Perspectives on Learning, 2013)
This paper aims to relocate our relationship to modes of knowledge that fall outside of Western rationalism and conceptual thought by relocating our understanding of agency through the figure of Anandamai Ma, a 20th century Hindu "saint.
Keywords: JAEPL; discursive agency; Anandamai Ma; avatara; Varanasi; India